VARIATION AND SYNONYMIC FEATURES OF SOCIO-POLITICAL TERMS IN THE TURKIC LANGUAGES - Dilmanov, Ilya Orakbaevich (SCIENCE and SOCIETY, 2026)
The article examines the features of variability and synonymy of socio-political terms in Turkic languages, taking into account their historical and modern development. The study identifies patterns in the use of terms in socio-political discourse and their role in shaping national language norms.
Keywords: Turkic languages; terminology; variability; synonymy; socio-political vocabulary; terminological system; internationalisms